FMEA method in operational reliability of forest harvesters - Kováč Ján (De Gruyter, 2020)
The article deals with the research of operational reliability of forest felling machines by FMEA method (Failure Mode and Effect Analysis). It describes collection of operational data and its analysis. It explains the procedure of realization for the method FMEA in the organization. Harvesters John Deere 1070D in the Company Lesy SR B. Bystrica were chosen for this research. The research was held in real operational conditions. Application of the FMEA method allows flexibility in case of unexpected situations and optimization of human potential abilities. FMEA tool is a tool preventing outages operational reliability and preventive tool for ensuring the maintenance of facilities. The method of information analysis mentioned below is simple ale precise enough for implementation in real working conditions.